The The Effect of Internal Locus of Control, Job Insecurity, and Job Stress on the Burnout of Non–Fulltime Teachers at Pamenang Selatan Elementary School - Rahman, K.A.; Muspawi, Mohamad; Fa'izah, Nurul (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
This study sought to ascertain the impact of internal locus of control, job stress, and job insecurity on burnout among South Pamenang's non-full-time teachers. This study employs quantitative research and is a form of survey research. The sample for this study comprised 50 respondents who were non-full-time teachers in South Pamenang. Employing the entire sampling method for sampling. The analytical techniques employed include multiple linear regression, path analysis, and a t-test with a significance threshold of 0.05%. According to the findings of this study, the value of t-count > t table, or 2,924 > 1.6794, and Sig. 0.05 or 0.005 0.05, whereas the t-table value is 1.6794. This indicates that the Burnout of non-full-time teachers in South Pamenang is influenced by an internal locus of control, job stress, and job uncertainty. Thus, it can be inferred that internal locus of control, job stress, and job insecurity all impact the Burnout of non-full-time teachers in South Pamenang.